Thesis & Dissertation Abstracts - ⠀, — (The Archive; Vol 5 No 1 (2024): Regular Issue Vol. 5, No. 1, 2024)
Modality in Ilocano by Benito V. Nolasco, Jr. A Grammatical Sketch of Porohanon by Vincent Christopher A. Santiago